New roles for old enzymes: killer caspases as the engine of cell behavior changes - Connolly, Patrick F.; Jäger, Richard; Fearnhead, Howard O. (Frontiers in Physiology, 2014)
It has become increasingly clear that caspases, far from being merely cell death effectors, have a much wider range of functions within the cell. These functions are as diverse as signal transduction and cytoskeletal remodelling, and caspases are now known to have an essential role in cell proliferation, migration and differentiation. There is also evidence that apoptotic cells themselves can direct the behaviour of nearby cells through the caspase-dependent secretion of paracrine signalling factors. In some processes, including the differentiation of skeletal muscle myoblasts, both caspase activation in differentiating cells as well as signalling from apoptotic cells has been reported. Here, we review the non-apoptotic outcomes of caspase activity in a range of different model systems and attempt to integrate this knowledge.